Andrzej Tomaszewski's "Pluralistic conservation philosophy" as a challenge: Do we have a problem with European identity? - Janusz Krawczyk (Ochrona Dziedzictwa Kulturowego)
In the well-known and frequently cited article by Prof. Andrzej Tomaszewski, Towards a Pluralistic Philosophy of Conservation in the 21st Century, from 2002, the history of heritage conservation was divided into three periods. The earliest was called the period of “primary pluralism” because the diversity of concepts and approaches to conservation issues resulted from the isolation of individual “cultural areas” on the world map. The specificity of the second period was determined by efforts to unify the theoretical foundations of conservation work by popularising European experiences and models which, as it was once believed, were universal. The third period, which Tomaszewski believed we entered at the beginning of the 21st century, should be a time of “universal pluralism”, and the contemporary philosophy of conservation, focused on the issues of protecting cultural diversity on a global scale, will no longer turn against local experiences and traditions. The article aims to analyse the assumptions of the pluralism postulated by Tomaszewski in the context of the development of heritage studies and the transformation of UNESCO's global conservation policy. The periodisation proposed by Tomaszewski will be used as a primary reference for analyses aimed at identifying those trends in contemporary conservation discourse that engage in polemics with Eurocentric views. In the summary of considerations on Eurocentrism, an attempt will also be made to answer whether the progressive relativisation of European conservation traditions and values ​​is equivalent to their invalidation as a starting point for new regional concepts for the protection and conservation of architectural heritage. The article will use the results of an analysis of UNESCO and ICOMOS documents, current research by conservation theorists and selected publications in contemporary heritage studies.